2012 6th International Conference on Signal Processing and Communication Systems 2012
DOI: 10.1109/icspcs.2012.6508024
|View full text |Cite
|
Sign up to set email alerts
|

UltraWideband wireless channel in presence of atmospheric gases and refined engine oil

Abstract: In this study we propose using Ultra Wideband Channel measurements to detect the presence of different substances between the antennas. This technique takes advantage of the large number of frequencies which an Ultra Wideband signal occupies. We propose two methods to detect differences in channel magnitude frequency responses when in the presence of different substances between the transmitting and receiving UWB antennas. We then take preliminary measurements and fit a curve of best fit to the processed data.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have shown that gases, solids, and liquids affect the electromagnetic wireless channel coefficients measured at individual frequencies . Vector Network Analyzers (VNA) is used with antennas to measure the individual complex wireless channel coefficients at a range of frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that gases, solids, and liquids affect the electromagnetic wireless channel coefficients measured at individual frequencies . Vector Network Analyzers (VNA) is used with antennas to measure the individual complex wireless channel coefficients at a range of frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that gases, solids and liquids affect the electromagnetic wireless channel coefficients measured at individual frequencies (Alshabo et al, 2012;Baghdady and Ely, 1966;Boan, 2007;Selmic et al, 2010;Shimomura et al, 2012;Wee et al, 2009;Yin-Chung and Porter, 1978;Micheli et al, 2015). Vector Network Analyzers (VNA) are used with antennas to measure a range of complex wireless channel coefficients at many different frequencies.…”
Section: Introductionmentioning
confidence: 99%